PENGARUH PROFITABILITAS, GROWTH OPPORTUNITY TERHADAP NILAI PERUSAHAAN dengan STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PROPERTY, REAL ESTATE &BUILDING CONSTRUCTION DI BEI Periode 2011 – 2014 - Nova Adhitya Ananda (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
This research is aimed at determining the effect of profitability, growth opportunity, and capital structure on the value of company. The object of this research is companies in the sector of property, real estate and building construction registered in Indonesian Stock Exchange during the period of 2011-2014. This research is using purposive sampling technique in determining samples. There are 37 out of 54 registered in the sector of property, real estate and building construction companies selected as the samples. The data were analyzed using partial least square (PLS) analysis. The research showed that growth opportunity and capital structure have direct significant effect on the value of company, while the profitability has not affected the value of company. Growth opportunity indirectly has positive effect on the value of company through the capital structure. Growth opportunity has positive effect on the capital structure. Profitability has positive and significant effect on the capital structure while capital structure has negative effect on the value of company.Key Words : Growth Opportunity, Profitability, Capital Struture And Value Of Company.